Prolonged Coma after Pituitary Macro- adenoma Surgery: A Case Report with Short Literature review - Karki, M.; Thapa, A.J.; Roka, Yam Bahadur (Nepal Medical College Journal, 2019)
Prolonged coma after surgery of pituitary macro-adenoma with apoplexy, often previously unnoticed, is rare and not well reported complication. A 65 year male presented with complaints of headache and blurred vision since few months. Brain MRI was done and it reported macro- adenoma with pituitary apoplexy. Right pterional craniotomy was done following total excision of tumor. Patient developed whole body seizure at first day of surgery and went to prolonged coma.